If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 5x + 4 = 15 Reorder the terms: 6 + 4 + 5x = 15 Combine like terms: 6 + 4 = 10 10 + 5x = 15 Solving 10 + 5x = 15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 5x = 15 + -10 Combine like terms: 10 + -10 = 0 0 + 5x = 15 + -10 5x = 15 + -10 Combine like terms: 15 + -10 = 5 5x = 5 Divide each side by '5'. x = 1 Simplifying x = 1
| 4y+1=22 | | 9x+10=-53 | | (2b+4)(b-3)=600 | | 3+3n-2n=4 | | 672x=175 | | 0=3n-3n | | 5(3)+3(3)-3+5= | | -6n+6n=4 | | 7-2(x+3)-x=x+5 | | n+n+(n-3+4)+4n=4n | | 6x^2+15x-25=0 | | f-f+9f-(f-3)=f+f | | 4m-12m+(m-3)=2m | | 3x+14+2x-4=90 | | -2-5(r-2)=-3(1-2r) | | 156-5x=31x+20 | | .833333x-.2x+4=.7x | | 506-?=265 | | 7(2n-4)-5=-40+7n | | 4ln(x-4)=4 | | (p+3)x^2+(2p+3)x+p+5=0 | | -.4x-9=.9 | | 5x+14=-28x-9x | | 19-3e=2-5(e+1) | | (y^2+2)(4y+7)= | | 2r^2+3r-20=0 | | (3y-3)(y+3)= | | 5x-3=2+6x | | 7=2r+5r | | -129=-3(8-7p) | | (y+9)(y+6)= | | 5x+1=14x-73 |